DR. SMILES AND THE "COUNTERFEIT" GENTLEMEN: SELF-MAKING AND MISAPPLICATION IN MID-NINETEENTH-CENTURY BRITAIN. Issue 1 (26th March 2018) - Matlock, Daniel
Abstract : On the morning of 15 May 1855, career criminal Edward Agar and his associate, William Pierce, walked away from the London Bridge Station of the South-Eastern Railway Company with over £14, 000 in stolen gold. The bullion was the property of the City of London merchants, whose intention had been to ship the bars via train to Dover and then on to Calais by ferry. Security was comprehensive and the success of Agar's en route interception was made possible only through labor-intensive planning and meticulous execution. It was the type of job in which the thief specialized. Even before what would become known as the "Great Bullion Robbery, " Agar's criminal diligence and self-drive had provided him with the monetary resources to establish himself in the wealthy, middle-class suburb of Cambridge Villas, where he enjoyed a reputation as a consummate gentleman. Throughout Agar's planning of the bullion heist, his neighbors remained entirely unaware that his home was headquarters to an extensive criminal ring.